Model Keputusan Pembelian Produk Dengan Menggunakan Celebrity Endorse Pada Platform Tiktok Di Universitas Dehasen Bengkulu - Kasari, Yosi; Irwanto, Tito; Putra, Iswidana Utama (Universitas Dehasen Bengkulu, 2025)
The development of digital technology, especially in social media such as TikTok, has brought significant changes in consumer behavior, especially in purchasing decisions for product. Along with the increase in social media, the presence of celebrity endorsers has a significant influence on consumer purchasing decisions. The purpose of this study is whether attractiveness, trustworthiness and expertise have an effect on purchasing decisions for product on Tiktok platform at Universitas Dehasen Bengkulu. This research method uses quantitative research and data collection using questionnaire techniques, with a sample of 120 respondents. The results showed that multiple linear regression Y = 20,924 + 0.253 X1 + 0.260 X2 + 2.546. Where the coefficient is positive, it means that there is a positive or unidirectional relationship between Celebrity Endorse variable (X1), Tiktok Platform (X2) value is 0 (zero), the purchasing decision (Y) Tiktok platform at Universitas Dehasen Bengkulu. The results show that the results of the Celebrity Endorse test (XI) show t count 3.894> t table 1.980 and sigfinication 0.000 t table 1.980 and sigfinication 0.005 2.45, it is concluded that it accepts the hypothesis, meaning that there is a simultaneous influence between Celebrity Endorse (XI), Tiktok Platform (X2) on purchasing decisions for Tiktok Platform at Universitas Dehasen Bengkulu. This can be seen at a significance level of 0.000 > 0,05.